Fractionated exposure to low doses of ionizing radiation results in accumulation of DNA damage in mouse spleen tissue and activation of apoptosis in a p53/Atm-independent manner. (1st February 2017) - Koturbash, Igor; Merrifield, Matt; Kovalchuk, Olga
Abstract: Purpose: While the effects of high doses of ionizing radiation (IR) are relatively well characterized, the molecular mechanisms underlying cellular responses to prolonged exposure to low doses of radiation remain largely under-investigated. Materials and methods: Here, we addressed the DNA damage and apoptotic response in the spleen tissue of C57BL/6 male mice after fractionated exposure to X-rays within the 0.1–0.5 Gy dose range. Results: The response to initial exposure to 0.1 Gy of IR was characterized by increased DNA damage and elevated levels of apoptosis. Subsequent exposures (cumulative doses of 0.2 and 0.3 Gy) resulted in adaptive response-like changes, represented as increased proliferation and apoptotic response. Cumulative doses of 0.4 and 0.5 Gy were characterized by accumulation of DNA damage and reactivation of apoptosis and apoptosis-related proteins. Additionally, spleen cells with irreversible damage caused by radiation can undergo apoptosis via activation of p38, which does not necessarily involve the Atm/p53 pathway. Conclusions: Fractionated exposure to low doses of X-rays resulted in accumulation of DNA damage in the murine spleen and induction of apoptotic response in p53/Atm-independent manner. Further studies are needed to understand the outcomes and molecular mechanisms underlying cellular responses and early induction of p38 in response to prolonged exposure to IR.